HYPOGLYCEMIC AND HYPOLIPIDEMIC EFFECTS OF ETHANOL ROOT EXTRACT OF CLERODENDRUM PHLOMIDIS IN ALLOXAN-INDUCED DIABETIC RATS - Dinesh Shanbhag, Mrunal; Radhakrishnan, Gowri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In traditional systems of medicine numerous plants have been used for the treatment and control of diabetes. Clerodendrum phlomidis is the accepted botanical source of the ayurvedic drug Agnimantha. The plant is used in the treatment of smallpox, inflammation, coryza, scrotal enlargement, syphilitic, and postnatal complaints. The roots are used to treat measles, gonorrhea, and diabetes. The present study aims at evaluating the hypoglycemic and hypolipidemic activity of C. phlomidis roots. Methods: Diabetes was induced by administering 120 mg/kg alloxan monohydrate intraperitoneally in albino Wistar rats for a treatment period of 21 days during which body weight changes and fasting blood glucose (FBG) were monitored at weekly intervals. On the 21st-day serum biochemical parameters, liver malondialdehyde, reduced glutathione, and glycogen levels were estimated. Results: The ethanol extract at 400 mg/kg dose significantly (p<0.001) reduced the elevated FBG and serum biochemical parameter levels. Conclusion: The present study substantiates the traditional use of C. phlomidis in the treatment of diabetes.